2005
DOI: 10.1096/fj.04-2558fje
|View full text |Cite
|
Sign up to set email alerts
|

17 β‐estradiol transiently disrupts adherens junctions in endothelial cells

Abstract: Interendothelial junctions are important regulators of endothelial cell functions such as migration and proliferation, major features in angiogenesis, and endothelial cell monolayer wound healing. 17beta-estradiol regulates these functions in vivo and in vitro and also increases endothelial monolayer permeability as it results from impaired monolayer integrity and intercellular adhesion. We hypothesized that 17beta-estradiol affects these cell adhesion-dependent functions in endothelial cells by targeting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 70 publications
0
32
0
Order By: Relevance
“…A number of studies have shown that inhibiting c-Src activity in breast cancer cells blocks estrogen-induced cell cycle progression and mitogenesis (33,34). Additionally, c-Src inhibitors have also been shown to block estrogen-induced migration in endometrial cells (35) and disrupt adherans junctions in endothelial cells (36). Thus, multiple biological phenotypes required for tumor progression may be converging and signaling through c-Src.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that inhibiting c-Src activity in breast cancer cells blocks estrogen-induced cell cycle progression and mitogenesis (33,34). Additionally, c-Src inhibitors have also been shown to block estrogen-induced migration in endometrial cells (35) and disrupt adherans junctions in endothelial cells (36). Thus, multiple biological phenotypes required for tumor progression may be converging and signaling through c-Src.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, physiological levels of 17b-estradiol increases endothelial permeability by mediating changes in intercellular junctions such as redistributing junction-forming proteins, increasing tyrosine phosphorylation of the adherens junction complex and disconnecting it from the cytoskeleton in a Src-family kinase dependent manner (40). Thus, transient changes in endothelial integrity provide a mechanism by which estrogen may modulate acute vascular events such as exudation and leukocyte recruitment in inflammation.…”
Section: Estradiol and Vascular Permeabilitymentioning
confidence: 99%
“…The midportion of each uterus was embedded in there are a few in vitro studies using vascular endothelial cells of various origins [13][14][15]. However, the actions of estrogen on paracellular permeability of vascular endothelial cells are different depending on the origin of vascular endothelial cells used for the studies [13][14][15].…”
Section: Double-immunofluorescence Methodsmentioning
confidence: 99%
“…However, the actions of estrogen on paracellular permeability of vascular endothelial cells are different depending on the origin of vascular endothelial cells used for the studies [13][14][15]. Therefore, to clarify the effects of estrogen on the paracellular pathway of vascular endothelial cells in the uterus, we investigated the in vivo effects of estrogen on the expression of VE-cadherin and claudin-5 in vascular endothelial cells in the endometria of murine uteri because the in vivo effects of estrogen reflect the physiological effects of estrogen more precisely than the in vitro effects of estrogen.…”
Section: Double-immunofluorescence Methodsmentioning
confidence: 99%